2021
DOI: 10.3748/wjg.v27.i26.4088
|View full text |Cite
|
Sign up to set email alerts
|

Non-occlusive mesenteric ischemia: Diagnostic challenges and perspectives in the era of artificial intelligence

Abstract: Acute mesenteric ischemia (AMI) is a severe condition associated with poor prognosis, ultimately leading to death due to multiorgan failure. Several mechanisms may lead to AMI, and non-occlusive mesenteric ischemia (NOMI) represents a particular form of AMI. NOMI is prevalent in intensive care units in critically ill patients. In NOMI management, promptness and accuracy of diagnosis are paramount to achieve decisive treatment, but the last decades have been marked by failure to improve NOMI prognosis, due to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 110 publications
1
26
0
3
Order By: Relevance
“…After studying the interesting article “Non-occlusive mesenteric ischemia: Diagnostic challenges and perspectives in the era of artificial intelligence” by Bourcier et al [ 1 ], who analyzed the current state of artificial intelligence (AI) in assisting clinical diagnosis and its possible application in diagnosing nonocclusive mesenteric ischemia, we are in full agreement with the AI techniques that the authors mention. However, a greater emphasis on the evaluation process for AI models could yield better results; when a rigorous testing stage is lacking, these models show poor performance upon transfer from the laboratory to real practice.…”
Section: To the Editorsupporting
confidence: 62%
“…After studying the interesting article “Non-occlusive mesenteric ischemia: Diagnostic challenges and perspectives in the era of artificial intelligence” by Bourcier et al [ 1 ], who analyzed the current state of artificial intelligence (AI) in assisting clinical diagnosis and its possible application in diagnosing nonocclusive mesenteric ischemia, we are in full agreement with the AI techniques that the authors mention. However, a greater emphasis on the evaluation process for AI models could yield better results; when a rigorous testing stage is lacking, these models show poor performance upon transfer from the laboratory to real practice.…”
Section: To the Editorsupporting
confidence: 62%
“…Right-sided colonic involvement has been associated with an increased need for surgical intervention and greater mortality. Early detection of bowel ischemia is critical for patient outcomes, and computed tomography is a frequently used modality for diagnosis [ 13 , 14 ]. A study by Nakamura et al found that pneumatosis intestinalis on CT imaging may represent a harbinger of irreversible bowel ischemia necessitating early exploratory laparotomy for definitive diagnosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important issue arises from the clinical course of our patient. The actual pathophysiology of NOMI remains unknown [ 3 ]; however, NOMI may occur simultaneously with renal vasoconstriction, which indicates a shared mechanism between these 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Nonocclusive mesenteric ischemia (NOMI) is a mesenteric circulatory disorder defined as diffuse intestinal ischemia in the presence of a patent arterial trunk [ 1 ]. Patients with NOMI account for 20–30% of patients with acute mesenteric ischemia, and NOMI has a mortality rate of 50–80% [ 2 , 3 ]. Elderly patients with NOMI should undergo multidisciplinary disease management, and surgery should always be pursued [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%